Development of multimedia-based learning media on safety and occupational health and environment (K3LH) material - Bijaksana Harefa; Envilwan Berkat Harefa; Arisman Telaumbanua; Aprianus Telaumbanua (Edumaspul: Jurnal Pendidikan, 2024)
The problem found by researchers through observations on the learning process at SMK Negeri 1 Mandrehe Barat, namely the learning process using media is still not optimal. The purpose of developing learning media in class XI-DPIB Based on Multimedia in the subjects of Basics of Building Construction and Land Measurement Techniques to determine the Feasibility, Practicality, and Effectiveness of Media Products. This type of research uses the ADDIE model (Analize, Design, Develompment, Implementation, Evaluation). The instruments used in this study were validation questionnaires for feasibility tests, student response questionnaires for practicality tests, and test essays for testing the effectiveness of learning outcomes. The results of this research are in the form of animated video-based media in the subjects of Basic Building Construction and Land Measurement Techniques. Very Feasible criteria based on 90% material expert assessment. Based on the assessment of linguists 98%. Based on the expert judgment of 95% Design. Media practicality is categorized as very practical based on 93% individual trials and 93% field trials. The criteria are very effective with a media effective percentage of 93%. So it can be concluded that the multimedia- based learning media developed is very feasible, practical, and effective to be used in the learning process. Suggestions from researchers (1) for students are expected with the existence of multimedia-based media to increase effectiveness and critical thinking in visible image material, (2) for educators can add innovation in using media (3) for researchers, can use this research as the next research to determine the feasibility of the product.